Options for reducing greenhouse gas emissions from agriculture and food systems - Martin, Will; Vos, Rob (International Food Policy Research Institute, 2024)
Food systems generate about one third of global greenhouse gas (GHG) emissions. Without reducing them, it will not be possible to stabilize the climate and keep the increase in global temperature below 1.5oC from pre industrial levels. About 50 percent of agricultural emissions (in CO2eq) comes from methane, a super potent GHG, mostly from livestock production and rice cultivation. We consider six broad approaches to emission reduction from agriculture—emission taxes, repurposing of farm subsidies, regulations, investing in green innovations, carbon credits, and demand-side interventions. We find that not only carbon taxes on agricultural production, but also rearranging agricultural subsidies will have only small impacts in terms of improving human and planetary health. Regulatory approaches, including conditionality and payment for environmental services (PES) can be counterproductive if they lower yields and require expansion of agricultural land use. Instead, we find that investing more in R&D for sustainable intensification of agriculture focused on productivity enhancing innovations have strong potential to generate major efficiency gains, drastic reductions in emissions and improved food security. Demand interventions designed to contribute both to environmental goals and improvements in health outcomes can play a supporting role. Since multiple sustainable development goals are to be achieved, no single instrument by itself will be effective. Instead, multiple policy instruments will need to be bundled and designed to create synergies and address trade-offs.